Strategy For Developing an Artificial Intelligence (Ai)-Based Air Defense Integrated System (ADIS) To Realize a Strong National Air Defense - Pallaguna, Anton; Winarna, Agus; BN, Sidik Dhani (The Eastasouth Journal of Social Science and Humanities, 2025)
This study discusses the Strategy for Developing an Air Defense Integrated System (ADIS) based on Artificial Intelligence (AI) in realizing a strong national air defense. The purpose of this study is to analyze the capabilities of ADIS, the use of AI technology and its development strategy in supporting the realization of a strong national air defense system. The method used is SSM analysis as the main method, the supporting method applied is Analytical Hierarchy Process (AHP). The results of the study indicate that the AI-based ADIS development strategy is an ecosystem model that can realize a solid, strong, independent, and sovereign air defense system, which is in accordance with the structure and characteristics of the Indonesian nation as an archipelagic country. The strategy for developing a strong air defense includes the formation of the National Air Defense System Posture (Sishanudnas) and System Integration, human resources (HR) in line with effective airspace management, accompanied by a doctrine that is able to adapt to the demands of technological progress and changes in the strategic environment that is always dynamic, and related to organizational aspects.